Epidemiology of Chagas' heart disease - Wanderley, Dalva Marli Valério (1995)
Chagas' disease is a major public health problem in Latin America. About 16 million persons are affected and 90 million others are exposed to the risk of being infected by the parasite. The knowledge of epidemiological aspects of the disease allowed to delineate the strategies for the control of the disease related with the vectorial transmission. However, these strategies have had no priority in all endemic countries. Rural-urban migration in most endemic areas carried infected individuals to urban centers increasing the problem of Chagas' disease by blood transfusion. In Brazil the control program has reached good results in the last years and in several states the vectorial transmission was controlled. More recently, hemotherapic practices are performed using screening procedures but this practice must be improved in order to eliminate the possibility of Chagas' disease transmission by another ways (congenital, accidental, oral, etc.). An adequate health care to the infected persons must be improved in order to diminish the social costs of the severe cardiopathy which has been responsible for the adults premature deaths.